KAJIAN PENGELOLAAN DANA KOPERASI SIMPAN PINJAM KONVENSIONAL DI KOTA SEMARANG - Sri Purwantini; Endang Rusdianti; Paulus Wardoyo (Jurnal Dinamika Sosial Budaya, 2016)
In accordance with the principles of cooperatives, Credit Union known as financial institution, as well as serve as an intermediary institution. Credit Unions activities include collecting deposits from members, gives loans to members, other cooperatives and or their members, as well as manage the balance of funding and lending.Based on the study results, it is found that Credit Unions can not rely on collection of funds from the member either in the form of savings, compulsory savings, time deposits. In addition, Credit Unions are also less interested in establishing a partnership with the Bank either through the linkage program and other programs.In an effort to balance of fund and loan portfolio, the manager of more use their experiences in the past, so that utilization is less than optimal. Weak regulation, has made the behavior of the manager of Credit Unions to act like a bank.